Smart waste management systems for sustainable urban life based on IoT for scalable IoT-based smart city solutions - Imon, Imran Hossain; Authro, Arnab Saha; Akter, Joya; Safina, Suzhat; Neha, Namreen Nayeem (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2023.